ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA BANK UMUM SYARIAH PERIODE 2016-2020 - Vania Salsabila, - (2021)
This study aims to determine the variables that affect the Financial Distress of Islamic Commercial Banks in Indonesia for the 2016-2020 period. The sample of this study was determined by purposive sampling method in order to obtain eleven Islamic Commercial Banks with a research period of five years and 55 observational data. The research method is descriptive quantitative with Logistics Regression Analysis Zmijewski model using SPSS 25 application. The data used is secondary data. The independent variables in this study are profitability, risk of non-performing financing, capital adequacy and liquidity, while the dependent variable is the financial distress of Islamic Commercial Banks. Based on Sharia Banking Snapshot data from the OJK, asset growth, financing disbursed growth and growth in sharia banking third party funds tended to decline from 2016 to 2020. Then in 2019 to 2020, the Covid-19 pandemic occurred which had a negative impact on the banking industry. and lead to a decrease in credit quality. The quality of loans disbursed is deteriorating and carries a high risk. The number of defaults on credit installments, both individual customers and business customers has increased. This causes banks to be more careful in carrying out their business activities to avoid financial distress. The solution from this research is to maintain banking financial ratios so that banking financial performance remains stable and in accordance with the criteria according to Bank Indonesia, so that banks can avoid financial distress. The results of the study based on data obtained from the annual financial statements of each Islamic Commercial Bank indicate that the profitability variable has no significant effect on the financial distress of Islamic banks, the risk of non-performing financing has a significant positive effect on the financial distress of Islamic banks, the adequacy of capital has a significant negative effect on the financial distress of Islamic banks and liquidity has no significant effect on the financial distress of Islamic banks in a negative direction.